2000
DOI: 10.2135/cropsci2000.404948x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tropical and Temperate Maize Populations Having Favorable Alleles for Disease Resistance

Abstract: A possible use of nonelite germplasm is as a source of alleles for disease resistance. Our objective was to determine the value of tropical and temperate maize (Zea mays L.) germplasm accessions as sources of alleles to improve disease resistance of the Corn Belt hybrid FR1064 × LH185. A group of tropical populations and hybrids from the Germplasm Enhancement of Maize Project (GEM) crossed to either Mo17 or B73 (temperate inbreds), was studied. In addition, a group of temperate accessions was evaluated. Reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…On the other hand, there was no significant difference between the other two hybrids in both seasons. These results are in agreement with those reported by Williams and Hallauer (2000); Kraja et al (2000) who showed that the difference of genotypes in disease severity was due to diversity in their genetic makeup.…”
Section: Table (4)supporting
confidence: 93%
“…On the other hand, there was no significant difference between the other two hybrids in both seasons. These results are in agreement with those reported by Williams and Hallauer (2000); Kraja et al (2000) who showed that the difference of genotypes in disease severity was due to diversity in their genetic makeup.…”
Section: Table (4)supporting
confidence: 93%
“…With few exceptions (Jiang et al, 1999; Zwonitzer et al, 2010), these studies used populations derived from crosses between two temperate adapted lines. Tropical lines tend to be more resistant than temperate lines to SLB and a number of other diseases due, presumably, to disease being a much more important selection pressure in tropical environments (Goodman, 1999; Kraja et al, 2000). Furthermore, with the exception of Kump et al (2011), each study reported results from analyses of single populations involving the segregation of alleles from two parents.…”
mentioning
confidence: 99%
“…For the five traits studied, PH207‐type inbreds are intermediate to the B73‐ and Mo17‐type inbreds and the Oh43‐ and A321‐type inbreds (Schaefer and Bernardo, 2013b). The Mo17‐type inbreds are known to be resistant to most leaf diseases (Kraja and White, 2000). The signs of the regression coefficients in Fig.…”
Section: Resultsmentioning
confidence: 99%